Alberta oil sands development and risk management of canadian boreal ecosystems - Carlson, M.; Stelfox, John (2014)
© Springer Science+Business Media New York 2014.The vast majority of Alberta's oil sands are yet to be developed due to the high cost of production, but declining conventional reserves will create high pressure to develop the resource. Simulation of the potential future effects of accelerated oil sands development demonstrates that associated increases in landscape disturbance, human access, and industrial activity would increase GHG emissions and elevate risk to fish and wildlife. These impacts can be reduced but not avoided by improving management practices and limiting non-industrial access. Expansion of the protected areas network is an additional mechanism to reduce environmental risk, and the aggregated distribution of bitumen deposits provides opportunities for cost-effective protection. The greatest land-use planning challenge presented by the oil sands is environmental values that are in direct conflict with oil sands production such as reducing greenhouse gas emissions or conserving wildlife such as caribou whose distribution overlaps bitumen deposits. A land'use plan has been developed for the region with the objective of optimizing the economic potential of the oil sands while also maintaining ecosystem function, biodiversity, and human health. If the land'use plan is implemented in its entirety, including the establishment of thresholds to limit land use within bounds of ecological integrity, it may provide a model for sustainable development of hydrocarbon reserves.